Comparison of Tuning Techniques for PID Controllers in Mobile Robots Using the Empirical Method and the Firefly Metaheuristic Algorithm - Silva, Lucas Marchesan da; Costa, Enzo Fernando Simão; Righi, João Pedro Azenha; Teles, Lucas; Silva, Thássio Gomes; Gamarra, Daniel Fernando Tello; Cukla, Anselmo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
Trajectory tracking remains a fundamental chal-lenge in mobile robotics, particularly for non-holonomic differential-drive robots such as those used in the IEEE Very Small Size Soccer (VSSS) competition. This work investigates and compares two control tuning approaches aimed at improving the performance of a VSSS robot in following a predefined path: the Firefly Metaheuristic Algorithm (FMA) and a traditional empirical method. The Bernoulli Lemniscate is adopted as the reference trajectory due to its variable curvature and suitability as a benchmark path in motion control tasks. Simulations in a virtual VSSS environment were conducted to evaluate tracking accuracy and system responsiveness under both strate-gies. Results show that FMA-based tuning leads to significant improvements in trajectory adherence and system stability. This study contributes to a deeper understanding of how systematic optimization methods can enhance control performance in small-scale autonomous robotic systems.